Morphological analysis of the brain subcortical gray structures in restless legs syndrome - Mogavero, Maria P.; Mezzapesa, Domenico M.; Savarese, Mariantonietta; DelRosso, Lourdes M.; Lanza, Giuseppe; Ferri, Raffaele (Sleep medicine, 2021)
Although several studies have shown the involvement of specific structures of the central nervous system, the dopaminergic system, and iron metabolism in restless legs syndrome (RLS), the exact location and extent of its anatomical substrate is not yet known. The scope of this new study was to investigate the brain subcortical gray structures, by means of structural magnetic resonance imaging (MRI) studies, in RLS patients in order to assess the presence of any volume or shape abnormalities involving these structures. Thirty-three normal controls (24 females and nine males) and 45 RLS patients (34 females and 11 males) were retrospectively recruited and underwent a 1.5 Tesla MRI study with two-dimensional T1 sequences in the sagittal plane. Post-processing was performed by means of the Functional Magnetic Resonance Imaging of the Brain Analysis Group Integrated Registration and Segmentation Tool (FIRST) software, and both volumetric and morphological analyses of the thalamus, caudate, putamen, globus pallidus, brainstem, hippocampus, and amygdala, bilaterally, were carried out. A statistically significant volumetric reduction in the left amygdala and left globus pallidus was found in subjects with RLS, as well as large surface morphological alterations affecting the amygdala bilaterally and other less widespread surface changes in both hippocampi, the right caudate, the left globus pallidus, and the left putamen. These findings seem to indicate that the basic mechanisms of RLS might include a pathway involving not only the hypothalamus-spinal dopaminergic circuit (nucleus A11), but also pathways including the basal ganglia and structures that are part of the limbic system; moreover, structural alterations in RLS seem to concern the morphology as well as the volume of the above structures. The role of basal ganglia in the complex neurophysiological and neurochemical mechanism of RLS needs to carefully reconsidered. •The exact location and extent of the anatomical substrate of RLS is not yet known.•Volumetric reduction in the left amygdala and left globus pallidus was found in RLS.•Surface of the amygdalae, hippocampi, caudate, globus pallidus, and putamen was abnormal.•The basal ganglia might play an important role in the mechanisms of RLS.